SAT0500 A Comparative Analysis of Radiological Findings between Tuberculous and Brucellar Spondylodiscitis. (15th July 2016) - Bouden, S.; Saidane, O.; Mahmoud, I.; Sahli, M.; Tekaya, R.; Abdelmoula, L.
Abstract : Background: Tuberculous and brucella spondylodiscitis are endemic in tunisia. Both present in various pathological patterns, but there are significant radiological differences that permit a presumptive aetiological diagnosis and orient the initial empirical treatment. Objectives: The aim of this study was to compare radiological features between these two diseases. Methods: A retrospective monocentric study was performed. Patients diagnosed with tuberculous spondylodiscitis (TSD) or brucellar spondylodiscitis (BSD) between 2008 and 2016 were included. Clinical status and radiological results were assessed. Results: A total of 33 patients were enrolled in the study including 17 men and 16 women. The mean age was 59 years (29–96 years). Twenty four had TSD (72, 8%) and 9 BSD (27, 2%). CT scan was performed in 9 cases and magnetic resonance imaging (MRI) in 24 cases. For both TSD ans BSD the most common region affected wad lumbar spine (respectively 58% and 77%). Preverebral, paravertebral, epidural and psoas abscess formations were significantly more frequent in TSD compared with BSD [p=0, 01]. When considering neurological complications such as epiduritis and cord compression, TSD was not significantly different from BSD [p=0, 17]. Conclusions: The results of this study show that TSD is a more suppurative disease with abscess formation. Disclosure of Interest: None declared